Elements of Expanded Core Curriculum That Best Predicts Academic Achievement of Students With Visual Impairment - Ntim, Edward Kofi; Vanderpuye, Irene; Kpodeo, Ivy Ama; Assie, Rebecca Afrah; Derkye, Charles (Advances in Social Sciences Research Journal, 2021)
Every student (student with visual impairment or non-student with visual impairment) is expected to leave the walls of any educational institution with a strong grasp of knowledge, skills, and attitude to function successfully in life-after-school. In order to be successful, students with visual impairment must learn all the nine components of the expanded core curriculum (ECC). The expanded core curriculum empowers students with visual impairment to access their education and make their own choices throughout life. Without specialised instruction in ECC, students with vision loss may not be aware of the activities of their peers or acquire other critical information about their surroundings (Ferrell, 2000). As students with visual impairment learn the expanded core curriculum they build a strong foundation for success in life today and tomorrow. The ECC must therefore, be strategically and sequentially taught and integrated into all aspects of the education of the student with visual impairment. Ninety three students with visual impairment at University of Cape Coast and University of Education, Winneba were used for the study. Questionnaire and Multiple regression were used to collect and analyse data respectively. Independent living skills emerged as the best predictor of academic achievement of students with visual impairment.